Strategi Penerapan Creative Paint Kits untuk Penguatan Literasi Kreativitas dan Pencapaian SDGS di Komunitas Pacitan Cerdas - Prasetyo, Abdul Rahman; Kusumaningrum, Shirly Rizki; Fajarianto, Otto; Ikhwan, Muhammad Zaenal; Al-Haq, Zulfikar (VISA: Journal of Vision and Ideas, 2025)
This study aims to describe the strategy of implementing Creative Paint Kits in improving creativity literacy and its contribution to the achievement of the Sustainable Development Goals (SDGs), especially in the aspects of quality education (SDG 4) and sustainable community development (SDG 11). This study was carried out in the Pacitan Smart Community which focuses on developing children's creativity through an art-based educational and participatory approach. The method used is qualitative descriptive with data collection techniques through participatory observation, in-depth interviews, and documentation of activities. The results of the study show that Creative Paint Kits not only play a role as a medium of visual exploration, but also as an educational tool that is able to encourage children's active participation in learning through art. The implementation strategy carried out includes the preparation of locally-based thematic modules, facilitator tr(Cahya & Purnanto, 2023)aining, and the involvement of parents and the surrounding community. This application directly encourages children to develop self-expression, improve fine motor skills, and understand socio-cultural issues contextually through visual works. Thus, the use of Creative Paint Kits makes a real contribution to the development of children's creative literacy, while encouraging the creation of a sustainable and inclusive learning community.